Resistance to Mycobacterium tuberculosis infection among highly TB exposed South African gold miners. - Violet N Chihota; Thobani Ntshiqa; Pholo Maenetje; Raoul Mansukhani; Kavindhran Velen; Thomas R Hawn; Robert Wallis; Alison D Grant; Gavin J Churchyard; Katherine Fielding (PLoS ONE)
Background Despite high exposure to Mycobacterium tuberculosis, a small proportion of South African goldminers resist TB infection. We determined, among long-service gold miners i) the proportion who were TB uninfected and ii) epidemiological factors associated with being uninfected. Methods We enrolled HIV-negative gold miners aged 33-60 years with ≥15 years' service and no history of TB or silicosis. Miners were defined as TB uninfected if i) QuantiFERON-TB Gold Plus (QFT-Plus) negative or ii) in a stricter definition, QFT-Plus-negative and zero-response on TST and as resisters if they were of Black/African ethnicity and negative on both tests. Logistic regression was used to identify epidemiological factors associated with being TB uninfected. Results Of 307 participants with a QFT-Plus result, median age was 48 years (interquartile range [IQR] 44-53), median time working underground was 24 years (IQR 18-28), 303 (99%) were male and 91 (30%) were QFT-Plus-negative. The odds of being TB uninfected was 52% lower for unskilled workers (adjusted odds ratio [aOR] 0.48; 95% confidence interval [CI] 0.27-0.85; p = 0.013). Among 281 participants of Black/African ethnicity, 71 (25%) were QFT-Plus negative. Miners with a BMI ≥30 were less likely to be TB uninfected (OR 0.38; 95% CI 0.18-0.80). Using the stricter definition, 44.3% (136/307) of all miners were classified as either TB uninfected (35; 26%) or infected, (101; 74%) and the associations remained similar. Among Black/African miners; 123 were classified as either TB uninfected (23; 19%) or infected (100; 81%) using the stricter definition. No epidemiological factors for being TB uninfected were identified. Conclusions Despite high cumulative exposure, a small proportion of miners appear to be resistant to TB infection and are without distinguishing epidemiological characteristics.